2019
DOI: 10.3390/ani9080550
|View full text |Cite
|
Sign up to set email alerts
|

The Opuntia effect and the Reactivation of Ovarian Function and Blood Metabolite Concentrations of Anestrous Goats Exposed to Active Males

Abstract: The effect of protein enriched Opuntia cladodes supplementation upon changes of serum total protein, urea, cholesterol, glucose as related to estrus induction (EI%), estrus latency (EL, h), and ovulation rate (OR, units) in adult anestrous goats exposed to the male effect was evaluated. In late April, anestrus goats (n = 45, 25° N) homogeneous regarding live weight (LE; 43.8 ± 1.6 kg) and body condition score (BCS; 2.3 ± 0.1 units) were randomly assigned to: (1). Protein-enriched Opuntia (PEO; n = 15; 29.8% CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…Interestingly, CP increases have been generated throughout a fermentation process of protein enrichment of Opuntia cladodes, from 12.8% (Aspergillus niger) [17], up to significant CP increases superior to 200% (Saccharomyces cerevisiae) [18]. Previous studies of our group demonstrated a positive out-of-season the effect in goats supplemented with protein-enriched Opuntia cladodes (i.e., the "Opuntia effect"), not only regarding estrus induction, estrus latency, and ovulation rate [19], but also upon corpus luteum number and diameter, as well as on embryo implantation rate [20]. Building on such ideas, our next step was to test the hypothesis that targeted supplementation of protein-enriched Opuntia megacantha Salm-Dyck cladodes during the last month of pregnancy and early lactation would improve the dam's glucose concentrations, augmenting both quality and quantity of colostrum and milk, as well as the kid metabolic status, and enhancing the kid-to-dam bonding behavior in low-input, rangeland-based goat production systems under semiarid conditions.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Interestingly, CP increases have been generated throughout a fermentation process of protein enrichment of Opuntia cladodes, from 12.8% (Aspergillus niger) [17], up to significant CP increases superior to 200% (Saccharomyces cerevisiae) [18]. Previous studies of our group demonstrated a positive out-of-season the effect in goats supplemented with protein-enriched Opuntia cladodes (i.e., the "Opuntia effect"), not only regarding estrus induction, estrus latency, and ovulation rate [19], but also upon corpus luteum number and diameter, as well as on embryo implantation rate [20]. Building on such ideas, our next step was to test the hypothesis that targeted supplementation of protein-enriched Opuntia megacantha Salm-Dyck cladodes during the last month of pregnancy and early lactation would improve the dam's glucose concentrations, augmenting both quality and quantity of colostrum and milk, as well as the kid metabolic status, and enhancing the kid-to-dam bonding behavior in low-input, rangeland-based goat production systems under semiarid conditions.…”
Section: Introductionmentioning
confidence: 80%
“…Goats consumed the available natural pasture and occasionally corn crop residues; they grazed daily from 10:00 a.m. to 06:00 p.m. and were penned at evening, with free access to mineral salts and water. The goatherd was managed according to the traditional procedures exerted by marginal goat producers in northern Mexico [19].…”
Section: Location Environmental Conditions and Goat Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…As in sheep, the age of the corpus luteum and, therefore, the day of the cycle in which PGF2α is administered determines the degree of synchronization obtained and the time required for the heat to appear, the LH peak and the ovulation [17]. Several studies indicate that goats treated on day 6 of the cycle go into heat and show an LH peak much earlier than those treated on day 12 [18,19].…”
Section: Will It Be Possible To Improve the Parameters Of Presence Ofmentioning
confidence: 99%